Single-Layer Versus Double Layer Intestinal Anastomosis of Small Bowel at Nepalgunj Teaching Hospital - Pathak, A; Rahaman, MD Aklakhur; Mishra, SM (Journal of Nepalgunj Medical College, 2015)
Background: Resection and anastomosis of small bowel is one of the common surgical procedure encountered in routine and emergency cases. There are various techniques of anastomosing the resected intestine. Objectives: To know the efficacy of single layer anastomosis over double layer anastomosis in terms of anastomotic leakage, wound infection, mortality and time consumed. Methods: A comparative cross sectional analytical study was carried out at department of General Surgery at Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke, Nepal from January 2013 to December 2013. Altogether 62 patients who underwent resection and anastomosis of small bowel were considered for this study. Patients who were included in this study were equally divided into two groups. Group A (n=32) underwent single layer anastomosis and group B (n=30) were subjected to double layer anastomosis. In both the groups anastomotic leakage, wound infection, mortality and time consumed were recorded and compared. Results: Altogether 62 patients were included in the study. The study showed anastomotic leakage 3 (9.37%) in Group A and 2 (6.67%) in Group B. Wound infection was 6 (18.75%) in Group A and 4(13.33%) in Group B and mortality was observed in only 1(3.12%) patient in Group A due to uncontrolled sepsis. There was no statistical difference between the two groups in anastomotic leakage, wound infection and mortality as shown by respective p (0.696, 0.562, 0.329) values. However the time required for single layer bowel anastomosis was less in comparison to double layer bowel anastomosis. Conclusion: Based on our data, the technique of single layer of bowel anastomosis does not increase the rate of anastomotic leakage, wound infection and mortality however time required for anastomosis is less as compared to double layer anastomosis. Therefore this study concludes that there is no added benefit of double layer of anastomosis over single layer bowel anastomosis. Journal of Nepalgunj Medical College Vol.12(1) 2014: 35-38